2019
DOI: 10.1002/anie.201902673
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Semiconductor Nanoparticles for Protein Catalysis and Profiling

Abstract: In this study,v ia as imple one-step method, chiral copper sulfide quantum dots (d/l-QDs) were prepared using d-/l-penicillamine (d-/l-Pen). The anisotropyfactor of d/l-QDs was as high as 0.01. The d/l-QDs can be used as photocatalysts to cleave proteins.N otably,t he l-QDs displayed the highest catalytic performance under left-circularly polarized light irradiation. Mechanistic investigations indicate the generation of hydroxylr adicals as the reactive species that cause the cutting of proteins.Chirality,whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 45 publications
1
77
0
1
Order By: Relevance
“…Because of their specific photochemical properties, chiral nanomaterials have become increasingly popular objects of research . Over the last decade, chiral nanoparticles (NPs) have been widely used in chiral catalysis, enantiospecific separation, chiral sensing, optical devices, and many other applications . More recently, chiral metal nanomaterials prepared with chiral amino acids or peptides have attracted significant attention due to their intense optical activities and good biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their specific photochemical properties, chiral nanomaterials have become increasingly popular objects of research . Over the last decade, chiral nanoparticles (NPs) have been widely used in chiral catalysis, enantiospecific separation, chiral sensing, optical devices, and many other applications . More recently, chiral metal nanomaterials prepared with chiral amino acids or peptides have attracted significant attention due to their intense optical activities and good biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
“…Kuang et al [149] reported the cleavage of BSA using Cu 2−x S QDs capped by D-/L-penicillamine, with this cleavage associated with generation of hydroxyl radicals as the reactive species. L-pen QDs displayed the highest catalytic performance under left-CPL irradiation, while D-pen QDs worked better under the right CPL irradiation.…”
Section: Chiral Biorecognition: Interaction Of Chiral Nanomaterials Wmentioning
confidence: 99%
“…The same is true of other chiral bio-active chemicals such as agrochemicals, pesticides and flavors. In recent years, researchers have also focused on the role of chirality in other areas such as catalysis [ 1 ], chiroptical applications [ 2 , 3 ], chiral magnetism [ 4 ], chiral semiconductors [ 5 ], cellular imaging [ 6 ], sensing [ 7 ], biomedical applications [ 8 ], chiral molecular assembly on surface [ 9 ], supramolecular chirality [ 10 ] and synthesis of chiral nanoparticles (NPs) [ 11 ]. One emerging field is chiral luminescent nanomaterials which have potential applications in chiral sensing [ 7 ].…”
Section: Introductionmentioning
confidence: 99%